Biomineralization and global change : A new perspective for understanding the end-Permian extinction - C. Garbelli; L. Angiolini; S. Z. Shen (Geology, 2017)
We investigated the kill mechanisms of the end-Permian mass extinction by analyzing patterns in biomineralization of marine invertebrates. The microstructures of Upper Permian brachiopod organocarbonate shells show the demise of the production of fabrics with a columnar layer-which has less organic matrix-in favor of more organic-rich shells at the end of Permian. Also, in the 100-120 k.y. interval prior to the Permian-Triassic boundary (PTB), the Rhynchonellata had small calcite structural units (fibers) and thus a higher shell organic content, whereas the Strophomenata were not able to produce smaller units. This suggests that the two classes had a different capacity to cope with environmental change, with the Rhynchonellata being more able to buffer against pH changes and surviving the PTB, whereas the Strophomenata became extinct. The observed trends in biomineralization are similar to the patterns in extant marine invertebrates exposed to increasing pCO2 and decreasing pH, indicating that ocean acidification could have been one of the kill mechanisms of the mass extinction at the PTB.